Re-framing AI: An AI Product Designer Perspective. - Fabrocini, Filippo; Terzidis, Kostas (Techné: Research in Philosophy & Technology, 2021)
AI is "essentially detached" from the world. The intrinsic nature of this technology precludes a proper space of negotiation between the different human and non-human actors involved and leads to an ideology of control. The challenge of the designer consists in looking across the black box, as opposed to looking inside, in order to visualise, sense, and experience why AI is leading us, and where, and how. These questions are as important as the algorithmic questions. The missing integration between human and artificial intelligence must be compensated for by mechanisms of social governance. These mechanisms should adopt an approach of constructive engagement with the limits of AI through the inclusion of social learning processes involving the different stakeholders, starting with ordinary citizens. Designing a "good" AI means to give up on a de-situated and socially detached understanding for engaging a community of actors while sharing a common concern.